Respuestas

2012-05-25T22:41:14+02:00

4x-6y=-3       (1)                                           4x-6y=-3

3x-3y=5        (2)    multiplicar por -2             -6x+6y=-10

                                                                  -----------

                                                                 -2x  =-13

                                                                    x=13/2

        Esto reemplazar en 1     4(13/2) - 6y = -3

                                                -6y= -3-26

                                                   y= 29/6